BIO-ECOLOGICAL AND ANATOMICAL ASPECTS OF THE EUROPEAN EEL ANGUILLA ANGUILLA (L. 1758) - PODDA, CINZIA (Università degli Studi di Cagliari, 2023)
Catadromous fish are considered important species for their ecological, economical, and cultural value. Because their complex life cycle, they are subjected to cumulative effects of anthropogenic threats that resulted in worldwide decline since the beginning of the 20th century. Among the most iconic catadromous species, the European eel Anguilla anguilla (L.) has aroused considerable interest since ancient times, though, to date, many aspects of its life cycle remain relatively unknown. A. anguilla showed a progressively decline since the 1970s. Starting from 2007, has been protected by the European Council Regulation 1100/2007, and successively classified as Critically Endangered (CR). Although conspicuous efforts have been conducted, to implement knowledge and identify possible solutions to preserve the future survivorship of A. anguilla, there is an urgent need to gain further insights into its life history. A review of the bibliography allowed me to obtain an updated state of the art of knowledge about the European eel life cycle, biology, ecology, allowing me to identify main topics that structured my thesis project. Topics have been developed with the general aim of providing a contribution to the implementation of the knowledge of the bio-ecology and anatomy of this species in relation to the various environmental and anthropic factors through a multidisciplinary approach that involved numerous sampling activities accompanied by complex data collection, laboratory experiments, and statistical analyses. First, I demonstrated the presence of synaptic development in the olfactory bulb, in terms of morphology and density of dendritic spines, that is shaped according to a pattern linked to the migratory life stages of the European eel (glass eels and silver eels). Second, I described the glass eels’ migration temporal peak for the first time in the central-western Mediterranean in relation to the effects of main environmental factors. I also identified a spatio-temporal variability between four sites in the ...